Legacy of the Anglo-Dutch Treaty 1824: Tracing its Impacts on the Present Time Indonesia and Malaysia’s Society and Legal Systems - Harefa, Jesslyn Elisandra; Akbar, Muhammad Rafie; Asto, Ari Ghazy Putra; bin Ibrahim, Muhammad Abdul Aziz (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2024)
The Anglo-Dutch Treaty of 1824 is a pivotal historical milestone, delineating territorial boundaries and shaping the trajectories of British and Dutch colonial empires in Southeast Asia. Beyond its geopolitical implications, this treaty exerted profound and enduring social effects on the indigenous populations of Indonesia and Malaysia. This article endeavors to elucidate the nuanced social consequences of the treaty, emphasizing its role in molding the fabric of societal life and legal frameworks in these two nations. Through a comprehensive analysis of the treaty’s stipulations, subsequent legal evolutions, and their ramifications on local communities, this study aims to unravel the intricate tapestry of influence that emanated from colonial decisions. Specifically, we delve into how the Anglo-Dutch Treaty of 1824 was pivotal in shaping the formation and development of social structures and legal systems in Indonesia and Malaysia. By scrutinizing the long-term effects on indigenous societies, this research contributes to a deeper understanding of the enduring impact of colonial legacies on the contemporary legal landscape of these nations. This article offers valuable insights into the lasting repercussions of a historical agreement that extended beyond mere territorial delineation. By exploring the intricate interplay between the treaty’s provisions and the subsequent socio-legal developments, we gain a nuanced understanding of the enduring ramifications of colonial decisions on the present-day legal frameworks in Indonesia and Malaysia.